The concept of object in literary works of Herta Müller - Andryanava, Katsiaryna V. (Journal of the Belarusian State University. Philology, 2019)
In this article the concept of object in H. Müller’s literary works is examined. The objects play a significant role in revealing a self-identification problem in the writer’s works. Images of certain objects can convey emotions and feelings of characters, and at the same time they represent a particular idea or symbolic meaning. In the works of H. Müller the objects, like people, have ambiguous nature: depending on a situation or a context, on the one hand, they can be seen as a saving remedy for loneliness, doubts, fear, death of the characters, and on the other hand as an instrument of the heroes’ obedience to those who have power.